Diversity of soil macrofauna in traditional oil mining of Wonocolo Geosite, Bojonegoro Geopark, East Java, Indonesia - LAILY AGUSTINA RAHMAWATI; NORMA AFIATI; THOMAS T. PUTRANTO (Society for Indonesian Biodiversity, 2024)
Abstract. Rahmawati LA, Afiati N, Putranto TT. 2024. Diversity of soil macrofauna in traditional oil mining of Wonocolo Geosite, Bojonegoro Geopark, East Java, Indonesia. Biodiversitas 25: 2148-2160. Wonocolo traditional oil mining has been going on for 130 years and has led to soil pollution. This study aims to characterize the composition of macrofauna in the soil affected by Wonocolo's traditional oil mining. The existence of macrofauna is important as a bioindicator of soil quality and its role in maintaining soil fertility levels. Mining areas are grouped based on the density of the oil well (rare, medium and dense), then three sample points are selected in each group. Macrofauna were collected using quadrat-hand sorting, pitfall trap, and flannel trap methods, and then the community structure index was analyzed. The results showed that 709 individuals were collected consisting of 17 orders and 71 species, with 64.8% of individuals found in category-dense areas. Hymenoptera and Polyrhachis sp. as the most abundant order and genus, while Odontomachus brunneus Patton 1894 is the most frequently encountered species. The average value of biodiversity, dominance, and evenness index ranged H'=1.28-1.57 (low), C=0.29-0.38 (low), and E=0.78-0.90 (high), respectively. Indications of environmental conditions in traditional oil mining areas cannot be seen solely from the value of the macrofauna biodiversity index but are apparent in the abundance of the Hymenoptera order in all areas categories and significant presence of Polyrhachis sp. species in the dense category.